Anion Defects Engineering of Ternary Nb-Based Chalcogenide Anodes Toward High-Performance Sodium-Based Dual-Ion Batteries - Liu, Yangjie; Qiu, Min; Hu, Xiang; Yuan, Jun; Liao, Weilu; Sheng, Liangmei; Chen, Yuhua; Wu, Yongmin; Zhan, Hongbing; Wen, Zhenhai (Nano-Micro Letters, 2023)
Sodium-based dual-ion batteries (SDIBs) have gained tremendous attention due to their virtues of high operating voltage and low cost, yet it remains a tough challenge for the development of ideal anode material of SDIBs featuring with high kinetics and long durability. Herein, we report the design and fabrication of N-doped carbon film-modified niobium sulfur–selenium (NbSSe/NC) nanosheets architecture, which holds favorable merits for Na+ storage of enlarged interlayer space, improved electrical conductivity, as well as enhanced reaction reversibility, endowing it with high capacity, high-rate capability and high cycling stability. The combined electrochemical studies with density functional theory calculation reveal that the enriched defects in such nanosheets architecture can benefit for facilitating charge transfer and Na+ adsorption to speed the electrochemical kinetics. The NbSSe/NC composites are studied as the anode of a full SDIBs by pairing the expanded graphite as cathode, which shows an impressively cyclic durability with negligible capacity attenuation over 1000 cycles at 0.5 A g−1, as well as an outstanding energy density of 230.6 Wh kg−1 based on the total mass of anode and cathode. Highlights: 1 We developed an efficient and extensible strategy to produce the single-phase ternary NbSSe nanohybrids with defect-enrich microstructure. 2 The anionic-Se doping play a key role in effectively modulating the electronic structure and surface chemistry of NbS2 phase, including the increased interlayers distance (0.65 nm), the enhanced intrinsic electrical conductivity (3.23 × 103 S m-1) and extra electroactive defect sites. 3 The NbSSe/NC composite as anode exhibits rapid Na+ diffusion kinetics and increased capacitance behavior for Na+ storage, resulting in high reversible capacity and excellent cycling stability.